2009
DOI: 10.1007/978-3-642-04645-2_25
|View full text |Cite
|
Sign up to set email alerts
|

On Profit-Maximizing Pricing for the Highway and Tollbooth Problems

Abstract: In the \emph{tollbooth problem}, we are given a tree $\bT=(V,E)$ with $n$ edges, and a set of $m$ customers, each of whom is interested in purchasing a path on the tree. Each customer has a fixed budget, and the objective is to price the edges of $\bT$ such that the total revenue made by selling the paths to the customers that can afford them is maximized. An important special case of this problem, known as the \emph{highway problem}, is when $\bT$ is restricted to be a line. For the tollbooth problem, we pres… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…For a cumulative pricing , the pricing subproblem can be shown to generalize the highway problem, which has been introduced by Guruswami et al and shown to be strongly NP ‐complete by Elbassioni et al . Thus, the following theorem holds.Theorem The cumulative pricing subproblem for an arbitrary zoning, that is, a connected or ring zoning, is strongly NP‐hard .…”
Section: Analysis Of Computational Complexitymentioning
confidence: 99%
See 1 more Smart Citation
“…For a cumulative pricing , the pricing subproblem can be shown to generalize the highway problem, which has been introduced by Guruswami et al and shown to be strongly NP ‐complete by Elbassioni et al . Thus, the following theorem holds.Theorem The cumulative pricing subproblem for an arbitrary zoning, that is, a connected or ring zoning, is strongly NP‐hard .…”
Section: Analysis Of Computational Complexitymentioning
confidence: 99%
“…For a cumulative pricing, the pricing subproblem can be shown to generalize the highway problem, which has been introduced by Guruswami et al [19] and shown to be strongly NP-complete by Elbassioni et al [12]. Thus, the following theorem holds.…”
Section: Np-hard Pricing Subproblemsmentioning
confidence: 99%
“…Algorithmic aspects of multidimensional pricing problems, which are important in the context of pure optimization as well as the design of revenue‐maximizing auction mechanisms [3], were first studied by Aggarwal et al [1] and Guruswami et al [24]. Subsequently, quite a number of improved algorithmic results for special cases of the problem [2, 12, 16, 17, 19, 20, 25] and complexity theoretic lower bounds [8, 18, 13] have been derived.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers have studied more complex and realistic user preferences in the complete information setting, with the aim of devising fast algorithms to give the optimal, or a good approximate, pricing solution [5][6][7][8][9][12][13][14][15][16][17][18][19]. Other researchers have studied the situation where the seller must set prices without knowledge, or complete knowledge, of the valuations of future users, with the aim of devising algorithms that will perform well even in the face of adversarial users trying to undermine the seller [1][2][3][4]10,11,20].…”
mentioning
confidence: 99%
“…Previous work has mainly focused on two supply models: the unlimited supply model [2,5,9,15,17] where the number of each type of item is unbounded and the limited supply model [2,[6][7][8]12,16,18,19] where the number of each type of item is bounded by some value. As for the users, there are several users' behaviors studied, including single-minded [12][13][14][15]17,19] (each user is interested only in a particular set of items), unit-demand [5][6][7][8][9]17,19] (each user will buy at most one item in total) and envy free [2,8,12,15,17] (after the assignment, no user would prefer to be assigned a different set of items with the designated prices, loosely speaking, each user is happy with his/her purchase). Most of the previous studies have considered a combination of the above scenarios (e.g.…”
mentioning
confidence: 99%